Improving student achievement : reforms that work - Solmon, Lewis C.; Agam, Kimberly Firetag; Schiff, Tamara Wingard, 1963- (Emerald Publishing Limited : Information Age Pub., 2005)
Improving Student Achievement: Reforms that Work expands on the first volume in the Milken Family Foundation series on education policy, Talented Teachers: The Essential Force for Improving Student Achievement. The series explains to policymakers, parents, business leaders, and teachers the importance of teacher quality in increasing student achievement. This volume is based primarily on the proceedings from the 2004 Milken National Education Conference (NEC), which was held in Washington, D.C., in May 2004.
Keywords: Academic achievement -- United States -- Congresses.; Teacher effectiveness -- United States -- Congresses.; Educational change -- United States -- Congresses.; elektronické knihy; Conference papers and proceedings.; Education -- Educational Policy & Reform -- General.; Educational strategies and policy.; electronic books